Clinical Response and Safety of Alternating Daily Dosage of Crizotinib due to Side Effects in Advanced NSCLC patient harboring ROS1-rearrangement: A Case Report - Jamal Zaini; Muhamad Rizqy Fadhillah; Sita Andarini (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: Advanced lung cancer has the lowest overall survival than other stage and tyrosine kinase inhibitor (TKI) are promising to prolong life and prevent disease progression. ROS1 rearrangement was very rare and constitute around 1.4 % of all NSCLC. Previous preclinical and clinical trial have reported the efficacy and safety of crizotinib against advanced NSCLC with ROS1 rearrangement, but little is known about its efficacy with nonstandard dosage.Case: A female, 58 years old, with no history of cancer nor smoking, came with persistent chest pain and cough for three months. The patient was then diagnosed with advanced lung cancer by FDG-PET CT Scan. The biopsy confirmed adenocarcinoma with genotyped ROS1-rearrangement. After receive standar dose of 200 mg bid, the patient intolerated and treatment plan was adjusted with 200 mg of alternated daily dosage (one-day on-off drug administration). Fortunately, the intolerance symptoms were alleviated and showed positive response during 3-years therapy.Discussion: Pulmonary tuberculosis has been linked to pneumothorax in HIV-associated TB patients. This study is done to better our understanding of the link between the two. The patient had active pulmonary tuberculosis as well as HIV and a rare case of bilateral pneumothorax in the ER.Conclusion: This case showed that advanced NSCLC with ROS1 rearrangement has positive response to crizotinib despite using alternating daily dose, with good response during 3 years and on.